Community-Based Tourism Development and Commodificiation in Sarugo Tourism Village - Ermayanti, Ermayanti; Rahman, Fajri; Irwandi, Ade (Humaniora: Journal of Indonesia Culture and Society, 2024)
The research objective was to explore the intersection of culture and tourism in Sarugo Village, West Sumatra. Specifically, the research aimed to elucidate this integration’s positive and negative impacts on the local culture to ensure cultural survival. The research sought to understand how cultural values were transformed into tourism products and services. The research employed an ethnographic approach, utilizing data collection methods such as observation and in-depth interviews with 15 participants. The research focused on the local community’s management of traditional houses, like Rumah Gonjong, which were transformed into homestays to accommodate overnight guests. The research results indicate that cultural aspects, crucial elements in the lives of people in Sarugo Village, are modified into tourism products. Specifically, Rumah Gonjong has been transformed into a homestay, demonstrating how the private sphere is converted into a public sphere within the tourism industry. This transformation has led to an economic increase for the local community, as the managers of the Rumah Gonjong now provide additional income. Consequently, the Rumah Gonjong is maintained, and the tourism industry’s consequences contribute to the cultural survival of the Sarugo Village community. Integrating culture and tourism in Sarugo Village highlights potential benefits and challenges, showcasing how sustainable tourism practices can preserve and promote local traditions.